If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (p)(p + 2) = 0 Reorder the terms: p(2 + p) = 0 (2 * p + p * p) = 0 (2p + p2) = 0 Solving 2p + p2 = 0 Solving for variable 'p'. Factor out the Greatest Common Factor (GCF), 'p'. p(2 + p) = 0Subproblem 1
Set the factor 'p' equal to zero and attempt to solve: Simplifying p = 0 Solving p = 0 Move all terms containing p to the left, all other terms to the right. Simplifying p = 0Subproblem 2
Set the factor '(2 + p)' equal to zero and attempt to solve: Simplifying 2 + p = 0 Solving 2 + p = 0 Move all terms containing p to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + p = 0 + -2 Combine like terms: 2 + -2 = 0 0 + p = 0 + -2 p = 0 + -2 Combine like terms: 0 + -2 = -2 p = -2 Simplifying p = -2Solution
p = {0, -2}
| 15x+-6=-51 | | -88(n-12)=2+(-89) | | 2(2x)=3(2x+y) | | x+0.07x=25.68 | | 0.003x-.2=0.01 | | V-9.12=7.55 | | 0.0196=m^2 | | -3y=20 | | x-6.34=35.1 | | -8x-9=9x+42 | | (u-8)(u-4)= | | 9+2(5m-3)= | | 3(x-1)=x+3 | | 2n+1=-31 | | 15y^2+25y+10=0 | | 2x+3(x+4)=12 | | -6k+8=-5k | | r^3-3r^2+2=0 | | G(x)=2x^2-6x-18 | | 4x^3+6x^2-18x+18=0 | | (-12x+6)+(x-15)= | | .94(x-2)=.02(6x-3)-.02 | | 0=-157+0.05v^2 | | -4(4p+2)-12=3(2p+8) | | x+50+3x=90 | | 3(c-1)+8=14 | | 5x-55=35 | | (9x+12)-(2x+8)= | | -11r=4r+55 | | -7x(t+4)=0 | | 8t+6t-t= | | 9-1/4n=15 |